FORMULATING COMPETITIVE STRATEGY IN MALANG CITY’S FOOD-BASED SOUVENIRS MARKET (STUDY AT PIA CAP MANGKOK MALANG) - MUHAMMAD ALMER REYHAN (Jurnal Ilmiah Mahasiswa FEB, 2018)
Strategy Formulation is a method that can be used to achieve the goals and objectives of a business by developing asustainable competitive advantage through which entered the market to serve the target market, while the factorsthat can affect strategy comes from internal factors and external factors. This study is made to formulatecompetitive strategies in the Pia Cap Mangkok Malang. This research is classified as descriptive qualitativeresearch and data collection techniques are carried out by observation, interviews, and documentation. Dataanalysis was performed using IFE Matrix analysis, EFE Matrix, CPM, IE Matrix, and QSPM.Based on the resultsof the IFE and EFE matrix analysis, the total IFE weighting score of 2.91 and EFE of 2.86 puts the Pia CapMangkok Malang in quadrant V, the strategy that can be implemented in cell V is Hold and Maintain. CPMidentifies that Pia Cap Mangkok Malang is in a strong position in a similar industry. The SWOT matrix results areknown that the company has several weaknesses in facing the threat. While promising market opportunities and theexternal environment also support companies to develop. The recommended strategy for companies in cell V ismarket penetration and product development. QSPM analysis produces a market penetration strategy as the mainstrategy of Pia Cap Mangkok Malang to increase its competitiveness. Keywords: Strategy Formulation, IFE, EFE, CPM, IE, SWOT, and QSPM